2010
DOI: 10.1016/j.jacc.2009.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Digital Assessment of Endothelial Function and Ischemic Heart Disease in Women

Abstract: RH-PAT indexes were significantly attenuated in women with IHD. Digital RH-PAT can predict patients with IHD, especially NOCAD before angiography. RH-PAT is potentially useful for identifying high-risk women for IHD. (Endothelial Dysfunction and Coronary Artery Spasm; NCT00619294).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
5
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(209 citation statements)
references
References 32 publications
(36 reference statements)
10
189
5
4
Order By: Relevance
“…This method has been validated and described previously in other populations16, 17, 18, 19, 20 and in patients with AF 21. After a 5‐minute baseline measurement, the blood pressure cuff on the test arm was inflated to 60 mm Hg above baseline systolic blood pressure or a maximum of 200 mm Hg for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been validated and described previously in other populations16, 17, 18, 19, 20 and in patients with AF 21. After a 5‐minute baseline measurement, the blood pressure cuff on the test arm was inflated to 60 mm Hg above baseline systolic blood pressure or a maximum of 200 mm Hg for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, finger plethysmography peripheral arterial tonometry has also been used. 42,43 Circulating levels of nitrite/nitrate, cyclic guanosine 3 0 ,5 0 -monophosphate, vascular cell adhesion molecule-1, intracellular adhesion molecule-1, monocyte chemoattractant protein-1, plasminogen activator inhibitor-1, von Willebrand factor, asymmetrical dimethylarginine, endothelial microparticles and progenitor cells are also measured as indices of endothelial function. 21,[44][45][46][47] However, these measurements do not directly reflect the production of NO from endothelial cells and are not 'function' .…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Matsuzawa, et al reported that RH-PAT index predicts the presence of Ischemic Heart Disease (IHD), especially non-obstructive coronary artery disease [24]. Vascular endothelial dysfunction was found in half of women with chest pain, in the absence of overt blockages in large coronary arteries, termed as coronary microvascular dysfunction.…”
Section: Vascular Endothelial Function and Coronary Artery Diseasementioning
confidence: 99%
“…RH-PAT has been tested in several clinical trials at multiple centers [18, 21,22]. The results from clinical trials have shown that RH-PAT could be useful for risk evaluation, stratification and prognosis of getting major cardiovascular events [18,20,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%